Treatment Patterns and Healthcare Resource Utilization among Patients with Advanced or Metastatic Soft Tissue Sarcoma in US Community Practices. (1st March 2020) - Nadler, Eric; Aguilar, Kathleen; Wentworth, Chuck; Boyd, Marley; Amirian, E. Susan; Barker, Scott; French, Pearl; Wilson, Thomas; Hess, Lisa M.
Abstract : Introduction . This study was designed to describe demographic and clinical characteristics of patients diagnosed with advanced or metastatic soft tissue sarcoma (STS) and to examine treatment and healthcare resource utilization patterns of this patient population in a United States (US) community-based oncology practice setting over time. Methods and Materials . A retrospective observational study was conducted within the US Oncology Network (USON). Patients were eligible if they were diagnosed with advanced or metastatic STS and were treated at a USON site between 01 July 2015 and 31 August 2018. Demographic, clinical, and treatment characteristics were described for the overall study population. Comparisons between patients by time period (prior to and after October 2016) were evaluated using the T test for continuous variables and chi-squared test for categorical variables. Data were available for analysis through 31 August 2018. Results . Demographic and clinical characteristics of the eligible study cohort ( N  = 376) were similar between patients who initiated treatment before and after October 2016 (all p > 0.05 ). Forty-three unique regimens were observed in the first-line setting, with the predominant regimen (gemcitabine + docetaxel) received by 33.2% ( n  = 125) patients. Prior to October 2016, 45.4% of patients received first-line gemcitabine + docetaxel, while 29.0% received this regimen after October 2016. Conclusions . While demographic and clinical characteristics were similar, treatment patterns changed in 2016. Future research should evaluate the impact of changing drug approvals and clinical trial results on future treatment patterns.